Micropropagation of Morus cathayana through in vitro culture from local Bogor, West Java, Indonesia - YASINTA RATNA ESTI WULANDARI; MENWANGI ADRIANASHINTA HARJOSUDIRJO (Smujo International, 2019)
Wulandari YRE, Harjosudirjo MA. 2019. Micropropagation of Morus cathayana through in vitro culture from local Bogor, West Java, Indonesia. Nusantara Bioscience 11: 18-22. Mulberry (Morus spp.) is a dicotyledonous plant known for its medicinal benefits as well as silkworm breeding (Bombyx mori L.) to produce silk. Morus cathayana mainly cultivated due to its high content of 1-deoxynojirimycin, widely utilized as an anti-diabetic agent. However, common practice in planting and maintenance of mulberry generate less profit, contributed to its long juvenile period and high heterozygosity level. Hence the development and cultivation through plant tissue culture techniques are necessary. The purpose of this research was to obtain the best combination of thidiazuron as a plant growth regulator. M. cathayana branches with nodal segments were used as explants. Research stages were explants initiation into Murashige and Skoog media, shoot induction in MS media as control and MS+BAP 1 mg/L+NAA 0.25 mg/L+TDZ 0.1, 0.5, 1 mg/L as treatment media, and statistical data analysis. Greater increase in shoot growth was observed in MS+BAP 1 mg/L+NAA 0.25 mg/L+TDZ 0.5 mg/L media, while the formation of shoots and calluses on the explants grown in control and treatment media showed no significant growth.